“Forum non conveniens” revisited: el caso Spanair - Llorente Gómez de Segura, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
This paper reviews a decision issued on March 22, 2011 by the United States District Court for the Central District of California in relation to the accident of a Spanair airplane at Madrid-Barajas airport on August 20, 2008. The decision applies the “forum non conveniens” doctrine and grants the motion to dismiss requested by defendants on the understanding that the Spanish courts will be a more convenient forum to try the facts. The analysis made by this paper shows the method of application of such doctrine and how it fits into the Barajas accident circumstances.
Keywords: Forum non conveniens; accident; aviation; Spain; United States